To answer this question, we need to remember that the linear combination method is a process in which we can add two equations in a way that one of the variables is eliminated, and, therefore, we can solve the equation for the other variable.
In this case, we have:
![\begin{cases}6g+8h=40 \\ -6g+2h=-20\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/kffg66c37s0y3jbo0a3uh6q6j9dxc0fzqz.png)
If we add both equations, we have:
![\begin{gathered} \frac{\begin{cases}6g+8h=40 \\ -6g+2h=-20\end{cases}}{0g+10h=20} \\ 10h=20 \\ (10)/(10)h=(20)/(10) \\ h=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/i1nwrnb095dprzr1bjae0o3ykbnquwgk5f.png)
Then we can substitute this value of h in one of the original equations to find g:
![\begin{gathered} 6g+8(2)=40 \\ 6g+16=40 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o1jwml9bpacn18w9funmotivop0nb63w96.png)
And to solve this equation, we can subtract 16 from both sides of the equation, and then divide both sides by 6:
![\begin{gathered} 6g+16-16=40-16 \\ 6g=24 \\ (6g)/(6)=(24)/(6) \\ g=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/joj9al802upqpohs0brt8xulvjmvs6zr58.png)
In summary, therefore, we have that the values are:
• g = 4
,
• h = 2